Trajectory and orbit of the unique carbonaceous meteorite Flensburg. (9th February 2021) - Borovička, Jiří; Bettonvil, Felix; Baumgarten, Gerd; Strunk, Jörg; Hankey, Mike; Spurný, Pavel; Heinlein, Dieter
Abstract: The C1‐ungrouped carbonaceous chondrite Flensburg fell in Germany on September 12, 2019, in the daytime. We determined the atmospheric trajectory, velocity, and heliocentric orbit using one dedicated AllSky6 meteor camera and three casual video records of the bolide. It was found that the meteorite originated in the vicinity of the 5:2 resonance with Jupiter at heliocentric distance of 2.82 AU. When combined with the bolide energy reported by the United States government sensors (USGS), the preatmospheric diameter of the meteoroid was estimated to be 2–3 m and the mass to be 10, 000–20, 000 kg. The meteoroid fragmented heavily in the atmosphere at heights of 46–37 km, under dynamic pressures of 0.7–2 MPa. The recovery of just one meteorite suggests that only a very small part of the original mass reached the ground. The bolide velocity vector was compared with that reported by the USGS. There is good agreement in the radiant but the velocity value has been underestimated by the USGS by almost 1 km s −1 .